Model Matematika SEIR Pada Kanker Kulit Akibat Paparan Sinar Ultraviolet Di Provinsi Sulawesi Selatan - Side, Syafruddin; Zaki, Ahmad; Rahmasari, Norliana (Jurusan Matematika FMIPA UNM, 2021)
This study aims to build a mathematical model of SEIR in skin cancer due to ultraviolet light exposure assuming that there is an incubation period in skin cancer. This model is divided into 4 classes namely susceptible, exposed, infected and recovered. The research procedure is carried out through the stages: make a SEIR model on skin cancer in the province of South Sulawesi, determine the equilibrium point of the model, analyze the stability of the equilibrium point, determine the base reproduction number ( ). The data used in building the model were skin cancer sufferers from 2018 to 2019 from Sudirohusodo Wahidin Hospital in Makassar. The results obtained that the greater the percentage of recovery rate of each infected individual due to treatment causes the population of the recovered class to increase and the population of the infected class to decrease. In other words skin cancer is not endemic in South Sulawesi Province.